RETRACTED: MicroRNA-200a Inhibits Inflammation and Atherosclerotic Lesion Formation by Disrupting EZH2-Mediated Methylation of STAT3 - Wang, Jinpeng; Li, Ping; Xu, Xiaofei; Zhang, Beilin; Zhang, Jing (Frontiers in Immunology, 2020)
Endothelial inflammation and dysfunction are critical to the process of atherosclerosis. Emerging evidence demonstrates that upregulation of miR-200a reduces VCAM-1 expression and prevents monocytic cell adhesion onto the aortic endothelium. However, limited information is available about the role of microRNA-200a (miR-200a) in facilitating atherosclerotic lesion formation. We investigated the anti-inflammatory and anti-atherosclerotic actions of miR-200a. Human umbilical vein endothelial cells (HUVECs) were cultured in the presence of oxidized low-density lipoprotein (ox-LDL), and their viability and apoptosis were evaluated using CCK-8 assays and flow cytomet-ric analysis. The enhancer of zeste homolog 2 (EZH2) promoter activity was evaluated in the pres-ence of miR-200a by dual luciferase reporter gene assay. EZH2-mediated methylation of signal transducer and activator of transcription 3 (STAT3) was validated by ChIP and IP assays. ApoE-/- mice were given 12-week high-fat diet and developed as in vivo atherosclerotic models. miR-200a was downregulated but EZH2 and HMGB1 were upregulated in ox-LDL-treated HUVECs and the aorta tissues of atherosclerotic mouse models. Elevated miR-200a was shown to protect HUVECs against ox-LDL-induced apoptosis and inflammation. EZH2 was verified as a target of miR-200a. The protective effects of miR-200a were abrogated upon an elevation of EZH2. EZH2 methylated STAT3 and enhanced STAT3 activity by increased tyrosine phosphorylation of STAT3, thereby in-creasing apoptosis and release of pro-inflammatory cytokines in ox-LDL-treated HUVECs. An anti-atherosclerotic role of miR-200a was also demonstrated in atherosclerotic mouse models. Our study demonstrates miR-200a has anti-inflammatory and anti-atherosclerotic activities dependent on the EZH2/STAT3 signaling cascade.